Nonporous platinum doped titania films: synthesis, optical and photocatalytic characteristics - D. V. Ihnatiuk; N. P. Smirnova; O. P. Linnik (Хімія, фізика та технологія поверхні, 2017)
The simple and fast route of the synthesis of platinum ions doped titania thin films is designed where platinum(II) acetylacetonate is used as a perspective doping agent due to the possibility of platinum incorporation in the form of the different valence states. Additionally, the multilayered films showing the varied properties are obtained. The increase in Pt content as well as the number of layers leads to the higher absorbance and the band edge shift to the red part of the spectrum. The indirect electronic transition is suggested and the calculated band gap values are depended on the film compositions as well as the number of layers. The significant decrease in the band gap value of titania is noted for 0.5 % Pt/TiO2 films. Pure titania and doped titania films contain anatase phase only with the average crystallite size near 14 nm. The conversion percentage of photocatalytic dichromate ions reduction is increased in the presence of three-layered 0.5 % Pt/TiO2 films under both UV and visible light. The activity of three-layered films is higher compare to the single layered samples. The film contained 0.1 % Pt exhibited the similar activity to titania one.